Online Flipbook for Facilitating Reading Activity in an Inclusive Class - Suputra, I Gede Riski (Journal of Educational Study, 2024)
This study aims to develop an interactive digital flipbook integrating visual elements, sign language, animations, and structured reading materials to enhance reading comprehension and engagement among fourth-grade students in an inclusive classroom. Specifically, this research explores the types of English reading media needed by inclusive students, the design of the flipbook for inclusive classroom use, its content validity, and its practicality. The study employed the ADDIE development model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. Data collection involved various instruments such as a need analysis interview guide, teacher and student interview guides, a researcher journal, a product development progress sheet, expert judgment sheets, and practicality questionnaires. The need analysis revealed that inclusive students, particularly those who are deaf and mute, require reading media that is visually rich, interactive, and accessible, with support such as sign language and minimal text complexity. The flipbook was designed with English reading activities, sign language integration, interactive elements, optional audio narration and the final product integrates audio, visuals, animations, and interactive elements to create a comprehensive and inclusive learning experience. The Flipbook not only supports the development of English reading skills but also promotes Pancasila values and national identity. Validation from content experts yielded an average score of 4.875 for content expert judgment and 4.6 for media expert judgment, categorized as "Very Good," indicating that the content was relevant, accessible, and supportive of inclusive learning goals. Practicality tests showed an average score of 4.38 from students and 4.5 from teachers, indicating that the flipbook was easy to use, engaging, and effective in improving reading comprehension. These findings highlight the potential of multimodal flipbooks as a valuable tool in inclusive education to improve learning access and outcomes for students with special needs.